(untitled) (Scientific journal of the Fergana State University, 2023)
The paper deals with analyzing the typical errors for a variety of reasons in teaching Uzbek students to write in English. The article focuses on the explanation of the linguistic psychological mechanisms of these “language errors”. This analysis in the frame of non-native English language pedagogic theory helps teachers to improve analyzing ability, linguistic knowledge and language skills of students and to improve the efficiency of the English as a foreign language teaching process.